Theragnostics - Alternative production of terbium isotopes at the University of Birmingham using an MC40 cyclotron. (December 2020) - Trinder, R. R.; Kokalova, Tz.; Parker, D. J.; Wheldon, C.; Phoenix, B.; Ivanov, P.; Russel, B.; Webster, B.; Regan, P.; Robinson, A.; Cullen, D.; Pells, S.; et al.
Abstract: In this work alternative methods for the production of terbium isotopes, and in particular 152 Tb and 155 Tb, have been investigated. These isotopes, which could be used for theragnostics, have been produced using an alpha and a proton beam incident on europium and gadolinium targets, respectively. The experimental results have been compared with the predicted cross-sections, calculated using TALYS and PACE4 code.